Effects of the FIFA 11+ injury prevention programme on physical and technical performance, biomechanical measures and physiological responses - Asgari, M.; Jaitner, T.; Nazari, B. (British Journal of Sports Medicine, 2021)
Background: Performance aspects of the FIFA11+ programme have not been generally reviewed. Objective: To synthetize the literature on the effects of the FIFA 11+ on the performance Setting Systematic review Participant:s Football players Search procedure: We searched five online databases for the period from 2006 to May. 2021, using five predefined keywords in conjunction to sub-keywords. Totally, 461 potential references recorded through Endnote and imported. Out of the 117 potential titles and abstracts screened by two independent researchers through Covidence, 54 full-text assessed for eligibility of which, 28 were included. Quality of studies and risk of bias were then assessed. Results: Studies carried out in 4 continents and 14 countries while recruiting female and male players aging range from 9 to 30. These indicate that the 11+ has been investigated worldwide. Quality of studies was moderate to high and except an unclear amount of bias for blinding outcome assessment; risk of bias for all domains was low. Excepting lower extremity stability, ankle evertors time latency and proprioception improvement, application of the 11+ at long-term (a complete football season) appeared to be successful in improving a variety of performance tests e.g. agility, sprinting, balance, jumping, cutting maneuvers etc; physiological responses and a majority of biomechanical measures. Vice versa, that the 11+ causes acute negative impact on the physical performance and technical abilities compared to the dynamic warm ups was highlighted in two studies. Conclusion: Application of the 11+ as warm up routine during trainings at long-term with higher adherence can be recommended for improving performance. However, caution must be observed while recruiting the 11+ for warming up before competitions as it may acutely decrease physical performance and technical abilities. Given the contradictory nature of the literature, further studies should evaluate short-term effects of the programme.